2013
DOI: 10.1177/1087054713486699
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hospital-Treated Injuries and ADHD Symptoms in Childhood and Adolescence

Abstract: The present study shows an association between hospital-treated injuries and symptoms of ADHD in a large epidemiological sample of 0- to 15-year-old children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 33 publications
4
42
1
Order By: Relevance
“…As mentioned above, there are also some studies that have shown that individuals in the United States afflicted with ADHD are more likely to be involved in accidents (DiScala et al, 1998;Merrill et al, 2009;Pastor & Reuben, 2006). Recent European studies have produced comparable results and added to the ongoing discussion (Hurtig et al, 2013;van den Ban et al, 2013). The aforementioned studies have contributed valuable information adding to the general knowledge of this area, but they had not yet succeeded in delivering results such as these using a representative sample of such substantial size, focusing on children and adolescents, considering a long period of time for potential accidents previous to the actual examination as well as differentiating between those being treated with ADHDspecific medication and those without such medication.…”
Section: Discussionmentioning
confidence: 94%
“…As mentioned above, there are also some studies that have shown that individuals in the United States afflicted with ADHD are more likely to be involved in accidents (DiScala et al, 1998;Merrill et al, 2009;Pastor & Reuben, 2006). Recent European studies have produced comparable results and added to the ongoing discussion (Hurtig et al, 2013;van den Ban et al, 2013). The aforementioned studies have contributed valuable information adding to the general knowledge of this area, but they had not yet succeeded in delivering results such as these using a representative sample of such substantial size, focusing on children and adolescents, considering a long period of time for potential accidents previous to the actual examination as well as differentiating between those being treated with ADHDspecific medication and those without such medication.…”
Section: Discussionmentioning
confidence: 94%
“…Further, other aspects, for example, the type of criminal offenses and overdose-related incidents, were included in the analysis. The variables were chosen according to previous work in this field, which showed that they might be associated with symptoms of ADHD: imprisonment [11,32], nicotine consumption [33,34], employment [35,36], gender [37,38], type of committed crimes [39], and hospital admissions [40]. High-risk drug use (e.g., Intravenous drug use, overdose-related incidences) was chosen as it has been shown to be associated with impulsivity [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that children with ADHD may demonstrate deficits in reaction time, fine and gross motor skills, and selected and sustained attention (20,22). Correspondingly, children with ADHD have been shown in multiple studies as having elevated risk for injuries ranging from fractures to sprains (17,27). Higher rates of positive results on screening tests for ADHD have been noted in patients with pediatric trauma compared with nontrauma patients (26).…”
Section: Neurocognitive Performance and Musculoskeletal Injury Riskmentioning
confidence: 99%